DUALISM IN THE STRANGE CASE OF DR. JEKYL AND MR. HYDE BY ROBERT STEVENSON: A DEMOLITION OF ALTER (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2018)
This final project is the analysis of the multiple personality disorder that reflected in the novel entitled The Strange Case of Dr. Jekyll and Mr. Hyde by Robert Stevenson. There are three objectives of this study. The first is to find out how does multiple personality disorder develop in the main character. The second is to find out how the main character deals with multiple personality disorder. And, the third is to find out the impacts of the disorder in character’s life. The analysis and the description of the data are provided to find the conclusion. The analysis of this study is using Freudian psychoanalysis theory. The study shows that the main character has two personalities. He can be Dr. Jekyll who is smart and kind or he can be Mr. Hyde who is cruel. This multiple personality disorder has the bad impacts to the character. His idea about dual human nature does not have support from his colleagues, even they deny it. It makes his relationship with his colleagues as scientist become worst. The multiple personality disorder also makes him being psychiatric disorder as his willing to do physical abuses in the form of Mr. Hyde in purpose to keep his reputation as Dr. Jekyll safe. In the end, the multiple personality disorder brings him to death. As stated in the novel he commits suicide to eliminate Mr. Hyde. These impacts affirm that multiple personality disorder causes a messy life psychologically and physically.